A Contract Contradiction - McLauchlan, David W (Victoria University of Wellington Law Review, 1999)
This article attacks the well established principle of the law of contract that evidence of the parties' negotiations and subjective intentions is not receivable in an interpretation dispute. It argues that the principle is inconsistent with equally well established principles of contract formation. Numerous other reasons for rejecting the principle, including the absence of convincing practical or policy grounds, are also identified and discussed. The author concludes that the courts should never enforce an agreement in accordance with a meaning which reliable evidence may show is contrary to the actual intentions of the parties.